Barriers to Pursuing Emergency Medicine Specialty Among Iranian General Practitioners: A Cross-Sectional Study - raaii, farzaneh; Tajaddini , Shahrad; Saberinia , Amin; Ahmadi Zarandi , Mohammad Hossein (Archives of Academic Emergency Medicine, 2025)
Introduction: Although emergency medicine is crucial globally, it remains underdeveloped in Iran, facing low recruitment rates. This study aimed to explore barriers deterring Iranian general practitioners (GPs) from pursuing emergency medicine as a specialty. Methods: A cross-sectional survey was conducted in Kerman, Iran, in 2023. Data were collected from GPs using a structured questionnaire assessing demographic characteristics and barriers to choosing emergency medicine. Statistical analyses, including chi-square and Mann-Whitney U-tests, were performed. Results: 198 GPs were involved in this study. 95.5% of the participants cited a mismatch between income and workload as the primary deterrent, while high psychological stress (87.4%) and limited private sector opportunities (86.9%) were also significant barriers. Additionally, 82.8% reported high burnout levels, with frequent night shifts (81.8%) and long working hours (75.3%) as contributing factors. Demographic analysis showed younger GPs and those with fewer years since graduation perceived financial and emotional strains more strongly, indicating that early-career physicians may feel more vulnerable to these challenges. Further, GPs lacking emergency department experience rated career uncertainties higher, suggesting unfamiliarity with the field might amplify negative perceptions. Rural GPs emphasized high patient loads and exposure risks, while urban GPs noted stress from crowded settings. Conclusion: Findings highlight financial and workload issues as major deterrents to choosing emergency medicine as a specialty. Addressing these concerns through better compensation, work-life balance improvements, and enhanced career prospects could attract more GPs to this specialty.